Enhanced Leaf Cooling Is a Pathway to Heat Tolerance in Common Bean - Deva, Chetan R.; Urban, Milan O.; Challinor, Andrew J.; Falloon, Pete; Svitákova, Lenka (Frontiers in Plant Science, 2020)
Common bean is the most consumed legume in the world and an important source of protein in Latin America, eastern and southern Africa. It is grown in a variety of environments with mean air temperatures of between 14 °C and 35 °C and is more sensitive to high temperatures than other legumes. As global heating continues, breeding for heat tolerance in common bean is an urgent priority. Transpirational cooling has been shown to be an important mechanism for heat avoidance in many crops, and leaf cooling traits have been used to breed for both drought and heat tolerance. As yet, little is known about the magnitude of leaf cooling in common bean, nor whether this trait is linked to heat tolerance. Accordingly, we explore the extent and genotypic variation of transpirational cooling in common bean. Our results show that transpirational cooling is an important heat avoidance mechanism in common bean. On average, leaf temperatures are 5 °C cooler than air temperatures, and can range from between 13 °C cooler to 2 °C warmer. We show that the magnitude of leaf cooling keeps leaf temperatures within a photosynthetically comfortable range. Heat tolerant genotypes cool more strongly than heat sensitive genotypes and the magnitude of this difference increases at elevated temperatures. Further, we find that differences in transpirational cooling are largest at the top of the canopy where determinate bush beans are most sensitive to the impact of high temperatures during the flowering period. We demonstrate that it is possible to accurately simulate the temperature of the leaf by genotype using only air temperature and relative humidity. Our work suggests that stronger leaf cooling is a pathway to heat tolerance. Bean breeders can use the difference between air and leaf temperature to screen for genotypes with enhanced capacity for heat avoidance. Once evaluated for a particular target population of environments, breeders can use our model for simulating leaf temperatures by genotype to assess the value of selecting for cooler beans.